Research on Digital Archives of Kunqu Opera in Chongqing and Protection of Intangible Cultural Heritage - Jin, Bohan John (Pinnacle Academic Press Proceedings Series, 2026)
Kunqu opera in Chongqing, as an important form of intangible cultural heritage that combines Bayu regional characteristics with classical Kunqu traditions, is currently facing multiple challenges in the process of digital preservation. Existing digital initiatives are largely confined to emergency documentation and basic recording, which leads to the omission of key performance skills, oral transmission practices, and contextual knowledge, thereby creating a potential crisis in long-term archival preservation. In addition, the lack of unified technical standards, fragmented and decentralized digital resources, and the absence of stable institutional and financial guarantee mechanisms significantly reduce the effectiveness and sustainability of protection efforts. This study analyzes the current situation of digital archiving of Kunqu opera in Chongqing, identifies core problems in technology, management, and resource integration, and proposes a framework for standardized technical systems and cross-regional resource-sharing platforms. It further discusses the potential of blockchain-based storage, long-term digital preservation strategies, and the construction of a comprehensive digital resource center to support both static preservation and dynamic transmission. By integrating multi-stakeholder participation and diversified support mechanisms, the research aims to promote the revitalization, dissemination, and innovative development of Kunqu opera performances in Chongqing in the digital era.